Supplementation with ready-to-use therapeutic food has no effect on adverse outcomes among undernourished children aged 6–59 months with severe pneumonia - Nalwanga, Damalie; Giallongo, Elisa; Musiime, Victor; Kiguli, Sarah; Olupot, Peter Olupot; Alaroker, Florence; Opoka, Robert; Tagoola, Abner; Hamaluba, Mainga; Mogaka, Christabel; Nabawanuka, Eva; Karamagi, Charles; et al. (Frontiers in Nutrition, 2025)
ObjectivesTo investigate the effect of supplementation with ready-to-use therapeutic food (RUTF) on adverse outcomes among undernourished children aged 6–59 months with severe pneumonia.MethodsThis secondary analysis of the COAST-Nutrition (ISRCTN10829073) included children hospitalized for severe pneumonia in Uganda and Kenya. Undernutrition was defined as having either a weight-for-age z score, height-for-age z score, or weight-for-height/length z score below the median of the WHO reference population (< 0) or mid-upper arm circumference (MUAC) below 13.5 cm. Participants were randomized to receive 1 sachet of RUTF daily for 8 weeks in addition to the usual diet (intervention) or usual diet alone (control). The primary composite outcome for adverse events was any one of mortality, re-admission, or deterioration of nutritional status by day 90 of follow-up.ResultsOf 846 main trial participants, 741 (88%) met the inclusion criteria (intervention: 374 versus control: 367). Of 687 (93%) participants in whom the primary outcome was assessed, 370 (54%) experienced an adverse event, [intervention: 184/348 (53%) versus control: 186/339(54%)]. There was no difference in the primary outcome between groups, aOR 0.92 (95% CI 0.68, 1.24), p = 0.572. Adverse outcome risk reduced with increasing age, aOR 0.53, (95% CI 0.45, 0.62), p < 0.001.ConclusionRUTF supplementation did not reduce the high frequency of adverse outcomes in children aged 6–59 months following hospital admission with severe pneumonia. Nutritional support directly targeting metabolic needs post-pneumonia should be considered in the future.Clinical trial registrationISRCTN10829073, PACTR202106635355751.